The Effectiveness of Using the Youtube Platform in Learning Videos Making Posters for Elementary School Students during the Covid-19 Pandemic - Jarizmy, Suniandra; Maryanti, Rina; Wulandary, Verra; Irawan, Asep Rudi (Jurnal Abdimas Kartika Wijayakusuma, 2021)
The spread of the Covid-19 virus in Indonesia is still happening. This causes all schools in Indonesia to apply distance learning. Various platforms make it easy for teachers to conduct distance learning for students, one of which is the Youtube platform. The purpose of this community service is to find out the effectiveness of using the Youtube platform in conducting learning through video. This method of community service uses a qualitative descriptive approach which is carried out through field observations and interviews. Based on the results of these activities, the use of the Youtube platform can be said to be effective in providing learning videos to make posters to elementary school students and the Youtube platform can be accessed for free by every student during this pandemic. Learning through videos makes students enthusiastic and enthusiastic while undergoing the learning process.